2019
DOI: 10.1093/deafed/enz039
|View full text |Cite
|
Sign up to set email alerts
|

Using the Adapted Flemish Sign Language Visual Communication and Sign Language Checklist

Abstract: This study addresses the topic of visual communication and early sign language acquisition in deaf children with a Flemish Sign Language (Vlaamse Gebarentaal or VGT) input. Results are obtained through a checklist focusing on sign-exposed deaf children’s visual communication and early sign language acquisition: the adapted VGT Visual Communication and Sign Language checklist. The purpose is to obtain the first detailed picture of these children’s visual and early VGT acquisition and to determine the optimal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The corpus has been analyzed by Loots (1999) ; Mouvet (2013) , Matthijs (2018) , and Wille (2018) for different research purposes and has given us a first and profound insight in the early interactions and language environment of deaf infants. Loots, for instance, concluded that parents who do not communicate visually and in a sequential manner with their deaf child stagnate in the transition from existential to symbolic intersubjectivity between the ages of 18 and 24 months ( Loots and Devisé, 2003a ; Loots et al, 2005a ).…”
Section: Beyond the Flemish Sign Language Corpusmentioning
confidence: 99%
See 1 more Smart Citation
“…The corpus has been analyzed by Loots (1999) ; Mouvet (2013) , Matthijs (2018) , and Wille (2018) for different research purposes and has given us a first and profound insight in the early interactions and language environment of deaf infants. Loots, for instance, concluded that parents who do not communicate visually and in a sequential manner with their deaf child stagnate in the transition from existential to symbolic intersubjectivity between the ages of 18 and 24 months ( Loots and Devisé, 2003a ; Loots et al, 2005a ).…”
Section: Beyond the Flemish Sign Language Corpusmentioning
confidence: 99%
“…In addition, Wille et al (2018) , who analyzed data collected by Mouvet and Matthijs, were the first to describe the VGT development of a deaf child growing up in a deaf signing family, with respect to dyadic face-to-face interactions. Along with a more extensive corpus analysis, using data from Loots (1999) , and Mouvet and Matthijs (2010–2013), this research provided the basis for the development of early interaction guidelines for professionals; including deaf children’s early visual milestones ( Wille et al, 2019 , 2020a , b ). The studies above, emphasize the benefits of a bimodal bilingual approach which can facilitate language development and may form a supportive basis for the children’s full language potential.…”
Section: Beyond the Flemish Sign Language Corpusmentioning
confidence: 99%
“…In a study involving ten Belgian parent-child dyads, the extent to which deaf parents and hearing parents use visual communications strategies during interaction with their 2-year-old deaf children was examined ( Wille, Allen, Van Lierde, & Van Herreweghe, 2019 ). Deaf fathers used more implicit strategies, such as waiting for a child to look to them for communication, compared to deaf mothers.…”
Section: Parental Stress and Copingmentioning
confidence: 99%